2D Transfer Function Modeling of Thermoacoustic Vibration Engines with Boundary Heat‐Flux Control. Issue 6 (14th May 2013) - Hong, Boe‐Shong; Chou, Chia‐Yu; Lin, Tsu‐Yu
Abstract In this paper we design a controllable type of thermoacoustic engine and model its process of energy transfer. In modeling, the conservation of thermoacoustic storage is formulated to determine engine cycles, capable of quantifying the effects of working gas and temperature on the power ratings, as well as shaping the engine chamber adaptable to mechatronic load in power transmission. Moreover, this conservation law can be applied to identify, through energy‐loss measurement, the parametric modeling upon flow leakage at the load end. Meanwhile, with the 2D transfer‐function modeling, the coupling of Rijke chamber dynamics and load dynamics is represented by feedback interconnection, which transforms the overall design into feedback systems synthesis. Based on such an internal feedback construction, digital signal processing is implemented to do numerical calculations on engine cycles with different working gases, temperatures, and frequencies of excitation, wherein typical situations are presented.